Rain fade and it's effect analysis for earth-to-satellite microwave link based on measured rainfall statistics in Bangladesh - Rashid, Mohammad Mahfujur; Islam, Md. Rafiqul; Alam, A. H. M. Zahirul; Khan, Sheroz; Khalifa, Othman Omran; Rahman, Md. Arafatur (2009)
The fast growth in communication systems has resulted congestion in lower frequency bands and microwave link designers are forced to explore higher and higher frequencies. Rain is a dominant source of attenuation at higher frequencies and consequently degrades the system performance in tropical and subtropical regions. The knowledge of rain fade and it’s performance is essential in order to optimize system capacity and meet quality and reliability. The rain intensity data is very essential to predict the rain fade at any location. The rain intensity data for Bangladesh is not available since it has not been measured so far. In this paper, one-minute integration time rain intensity data are derived from forty years measured annual rainfall statistics. The converted rain intensity data are used to estimate rain fades at C, Ku and Ka-bands. The rain fade is also estimated using ITU-R recommended rain intensity. Noise generated during rains are predicted for all three bands and carrier-to-noise ratios are estimated to compare the performances of earth-to satellite link at different frequency bands in Bangladesh.